Optimizing Accounting Information Systems for Enhanced Business Sustainability - Nadhia Fortuna Chotrianda (Arthatama: Journal of Business Management and Accounting, 2024)
The integration of Accounting Information Systems (AIS) has become imperative for modern businesses seeking to enhance operational efficiency, risk management, and financial transparency. This study employs a qualitative approach with case studies to examine the impact of AIS implementation on business sustainability. Data collection methods include structured interviews, direct observations, and document analysis, with content analysis techniques applied for interpretation. Findings indicate that optimal AIS utilization streamlines accounting processes, minimizes errors, and improves financial reporting accuracy. Additionally, AIS plays a crucial role in mitigating financial and operational risks through real-time data analysis and strengthened internal controls. The study underscores the managerial importance of aligning AIS with business strategy and investing in workforce training to maximize its benefits. These insights contribute to the existing literature by providing empirical evidence on AIS's role in sustainable business practices and proposing future research directions on its long-term effectiveness across various industries.